Polyoxometalate Intercalated M2+/Al (M2+=Ni, Mg) Layered Double Hydroxide for Degradation of Methylene Blue - Yulizah Hanifah; Mardiyanto Mardiyanto; Risfidian Mohadi; Nur Ahmad; Suheryanto Suheryanto; Aldes Lesbani (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
The synthesis and characterization of M2+/Al (M2+=Ni, Mg) layered double hydroxide (LDH) and intercalated polyoxometalate is presented. We have reported the growth of polyoxometalate on Ni/Mg layered double hydroxide for degradation methylene blue (MB). By considering variables such as pH of dye solution, dye concentration, and time as degradation variables, the efficiency of organic dye degradation and degradation parameters of M2+/Al (M2+ = Ni, Mg) LDH and both composite LDH-polyoxometalate has been identified. X-Ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), Scanning Electron Microscope (SEM), and Ultra Violet Diffuse Reflectance Spectroscopy (UV-DRS) spectroscopy confirmed the layered double hydroxide structure. XRD and FTIR analysis confirmed the single-phase of the as-made and polyoxometalate intercalated LDH. SEM images show the formation of aggregates of small various sizes. The material’s photodegradation was assessed through methylene blue (MB) degradation process. The result showed that NiAl-Si has a good degradation capacity for MB as compared to NiAl-Pw, MgAl-Si, and MgAl-PW. The result shows that LDH composite presents stability and has good photocatalytic activities toward the reduction of methylene blue. The FTIR measurement confirming the LDH composite structure reveals the materials used in the fifth regeneration. The activity of MB photodegradation pristine were NiAl (45%), MgAl (43%), NiAl-Pw (78%), NiAl-Si (85%), MgAl-Pw (58%), and MgAl-Si (75%), respectively. The LDH-polyoxometalate composite material’s capacity to successfully photodegrade, as measured by the percentage of degradation, revealed an increase in photodegradation catalysis and the ability of the LDH to regenerate. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).